The relevance of sleep and circadian misalignment for procrastination among shift workers - KUHNEL, Jana (Institutional Knowledge at Singapore Management University, 2018)
This daily diary study contributes to current research uncovering the role of sleep for employees' effective self-regulation at work. We focus on shift workers' effective self-regulation in terms of their general and day-specific inclination to procrastinate, that is, their tendency to delay the initiation or completion of work activities. We hypothesized that transitory sleep characteristics (day-specific sleep quality and sleep duration) and chronic sleep characteristics in terms of circadian misalignment are relevant for procrastination. Sixty-six shift workers completed two daily questionnaires over the course of one work week, resulting in 332 days ofanalysis. Results of multilevel regression analyses showed that on days when shift workers slept better and longer-compared to days when they slept worse and shorter-they had more energy and willpower available after sleep and subsequently were less prone to procrastination. Moreover, the more work times (permanent shift) were misaligned with employees' sleep-wake preferences (chronotype) the more pronounced was shift workers' inclination to procrastinate at work. The present findings provide important implications for shift workers' effective functioning at work. Practitioner Points: To promote shift workers' effective functioning at work, when scheduling shift work, circadian principles should be taken into account, and work times should be aligned with workers' chronotypes. Day-specific sleep quality and duration co-vary with procrastination at work. Thus, on days on which procrastination would be especially harmful, sleep of good quality and of sufficient duration should be obtained.